Chromosome Mapping of H1 Histone and 5S rRNA Gene Clusters in Three Species of Astyanax (Teleostei, Characiformes) - Hashimoto, D. T. [UNESP]; Ferguson-Smith, M. A.; Rens, W.; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Karger, 2011)
We report here on the physical mapping of the H1 histone genes (hisDNA) and the 5S ribosomal DNA (rDNA) in 3 Neotropical fish species of the genus Astyanax (A. altiparanae, A. bockmanni and A. fasciatus) and the comparative analysis of the chromosomes bearing these genes. Nucleotide analyses by sequencing of both genes were also performed. The distribution of the H1 histone genes was more conserved than that of the rRNA genes, since these were always located in the pericentromeric regions of 2 chromosome pairs. 5S rDNA was found on one of the pairs that presented an H1 histone cluster; this seems to be a conserved chromosomal feature of the genus Astyanax. In addition, individuals of A. bockmanni and A. fasciatus showed clusters of 5S rDNA on 1 pair of acrocentric chromosomes, not found in A. altiparanae. The results obtained by chromosome mapping as well as by sequencing of both genes showed that A. bockmanni is more closely related to A. fasciatus than to A. altiparanae. The results allow the characterization of cytogenetic markers for improved elucidation of the processes involved in karyotype differentiation of fish genomes. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Astyanax; Fish cytogenetics; H1 histone; Repetitive DNA; 5S ribosomal DNA